Ethical values in Malay woodcarving : a case study of Wan Mustaffa Wan Su's work / Mohd Suhaimi Tohid - Tohid, Mohd Suhaimi (2006)
Traditional woodcarving is the most significant Malay ornamental art. The creative expressions of the Malay woodcarving are very much influenced by the religious, moral and ethical values of the craftsmen, which are developed as an act of submission to the All Mighty. The ethical issues involved are mostly connected with the worldview of the Malays. - The study of this research examines the practical aspects that explain the creative and aesthetic aspirations of a Malay woodcarver named, Wan Mustaffa Wan Suo The study will focus on his attitudes towards philosophy, aesthetics and the creative process in executing his work. It is hoped that the study would provide useful evidence of the existence of ethical values on Malay traditional woodcarving. The findings could serve as valuable references for researchers who are concerned with the study ofMalay traditional art ofwoodcarving. The methodology used is based on the qualitative approach to research. Since each individual has his own reality about life, this study emphasizes the identification of the philosophy that evolves and guides the worldview of Wan Mustaffa Wan Suo The purpose here is to capture his experience and how he interprets it in his work. Data collection and analysis are gathered through a variety of means such as observation, interview, photograph and written description. Data collection occurs concurrently with data analysis, where the explanations provided by the woodcarver are analysed and interpreted. Chapter 1 provides the introduction, background, objectives of the study, significance of the study, statement of the problem, limitation, and the research methodology like interviews, description of the work and artefacts. Chapter 2 focuses on the review of related research and literature. A brief account of the study on the traditional art of Malay woodcarving and the development of Malay 'ethical values are addressed. Chapter 3 concentrates on the theoretical background on the case studies and interpretation that describes the concept of traditional art, the interpretation of symbols in the design motifs and the influence of Islam in the work of the Malay woodcarvers. Chapter 4 provides data analysis on the study of the ethical values that governs the interpretations of the Malay woodcarving. An analysis and interpretations of the woodcarvings ofWan Mustaffa Wan Su are included. Chapter 5 describes the analysis, result and conclusion of the study ofWan Mustaffa Wan Su's woodcarvings. The study shows that there is a strong influence of Islamic teachings, philosophical views and ethical values in the work of Wan Mustaffa Wan Su.